Media Ethics: Identifying Ethical Issues and Resolving Ethical Dilemmas - Yesudhasan, Thomas (Univeristy Technology Mara (UiTM), 2020)
This paper investigates the importance of ethical practices in journalism by critically looking at what media ethics is all about and how to resolve ethical dilemmas. Moreover, asks an important question: why do journalists often tend to ignore ethical principles and tweak the news stories? This paper answers these questions by applying various moral philosophies, codes of ethics, frameworks such as Kantian and Virtue Ethics and by referring to relevant case studies. This paper intends to deliberate the need for and importance of ethics in journalism.